Jeszcze raz o funkcji aojdy na dworze Agamemnona (Odyseja III 263-272) - Korus, Kazimierz (Vox Patrum, 2016)
This paper looks at two accounts of scholars’ views on the bard as the custodian of Homeric Society (Odyssea III 263-272). The first traditional, defended by Stephen P. Scully, sees a singer, an unnamed singer, as a moral guard of Clytaemnestra. The second, defended by Stephanie West, suggests that it is worth an alternative explanation, rejected in the scholia but perhaps reflected (or corroborated?) in Hesychius’ Lexicon where ¢oidÒj is glossed with eÙnoàcoj, sp£dwn. She says that the word e„rÚsqai (Odyssea III 268) suggests rather physical protection though a bard sufficiently able-bodied is an effective guardian might himself be tempted to rape or seduction. The Author of the article defends traditional understanding of the role of bard with many other arguments. He is convinced that the singer was removed from the palace because his presence reminded Aegisthus and Clytaemnestra of their wrong to society.